Bibliometric Analysis of TPACK Publication Trends in Scopus Data Base from 2013 to 2022 - Nasir; Hartono Bancong; Sukmawati; Uyunnasirah Hambali (Studies in Learning and Teaching, 2023)
This study aims to find out the development of the publication of scientific articles about the TPACK (Technological Pedagogic Content Knowledge) Model. The research method used was a literature review using a bibliometric analysis approach that started by searching the TPACK model keywords in the Scopus journal database from 2013 to 2022. The study results revealed that within a period of 10 years, from 2013 to 2022, there were 528 publications of the TPACK model published in Scopus-indexed journals. Meanwhile, the United States is the country that contributes the most to the number of published articles. The Journal of Physics Conference is listed as the journal that has contributed the most to the dissemination of the Scopus-indexed TPACK model articles. To get more comprehensive results, further research is not only limited to Scopus-indexed journals but also includes the integration of the TPACK component in the learning to be studied.